2006
DOI: 10.1352/0895-8017(2006)111[15:pfaveo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving Facial and Vocal Expressions of Emotion in Individuals With Williams Syndrome

Abstract: People with Williams syndrome are extremely sociable, empathic, and expressive in communication. Some researchers suggest they may be especially sensitive to perceiving emotional expressions. We administered the Faces and Paralanguage subtests of the Diagnostic Analysis of Nonverbal Accuracy Scale (DANVA2), a standardized measure of emotion recognition for basic emotions to three groups: adolescents and adults with Williams syndrome, age and IQ-matched participants with learning/intellectual disability, and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
97
5
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 35 publications
16
97
5
1
Order By: Relevance
“…Studies that have employed eye tracking techniques have provided evidence that individuals with WS demonstrate a reduced ability to disengage attention from the eye region of a face when compared to mental-age (MA) matched controls Riby & Hancock, 2009). In addition, emotional expressions of faces have been shown to influence attention allocation, with positive (happy) emotions yielding greater visual attention than negative emotions (fearful, angry) in faces (Dodd & Porter, 2010;Plesa-Skwerer, Faja, Schofield, Verbalis, & Tager-Flusberg, 2006;Santos, Silva, Rosset, & Deruelle, 2010). The findings of atypical attention to positive emotional faces, specifically the eye region of faces in WS, are consistent with previous evidence of the role of the amygdala in directing visual attention (Gamer & Buechel, 2009;Gamer, Zurowski, & Buechel, 2010).…”
supporting
confidence: 84%
“…Studies that have employed eye tracking techniques have provided evidence that individuals with WS demonstrate a reduced ability to disengage attention from the eye region of a face when compared to mental-age (MA) matched controls Riby & Hancock, 2009). In addition, emotional expressions of faces have been shown to influence attention allocation, with positive (happy) emotions yielding greater visual attention than negative emotions (fearful, angry) in faces (Dodd & Porter, 2010;Plesa-Skwerer, Faja, Schofield, Verbalis, & Tager-Flusberg, 2006;Santos, Silva, Rosset, & Deruelle, 2010). The findings of atypical attention to positive emotional faces, specifically the eye region of faces in WS, are consistent with previous evidence of the role of the amygdala in directing visual attention (Gamer & Buechel, 2009;Gamer, Zurowski, & Buechel, 2010).…”
supporting
confidence: 84%
“…This prolonged attention to faces has been observed in both toddlers with the disorder (Mervis et al, 2003) and has been shown experimentally with older individuals who have WS using eye tracking (Riby & Hancock, 2008). This prolonged attention to a person's face does not, however, lead to an increase or heightened proficiency at interpreting information from that face, such as cues as to how the person is feeling (Plesa-Skwerer, Faja, Schofield, Verbalis, & Tager-Flusberg, 2006a) or where they might be attending (Riby, Hancock, Jones & Hanley, 2013). This is particularly important, as increased drive for social interaction (Jones et al, 2000), a lack of understanding of the dangers associated with interactions with unfamiliar people (e.g.…”
Section: Introductionmentioning
confidence: 77%
“…Participants with WS generally recognised mental states at the level expected by their verbal ability, which was poorer than expected from their CA (Plesa Skwerer et al, 2006a). However, they had some specific difficulties.…”
Section: Mental State Judgementsmentioning
confidence: 83%
See 1 more Smart Citation
“…This has led researchers to conclude that the social profile in WS might be uneven as well with the social perceptual components being intact but the socio-perceptual component being impaired (Tager-Flusberg and Sullivan 2000). However, more recent studies have found that participants with WS also show difficulties on tasks that tap into socio-perceptual abilities (for example Plesa-Skwerer et al 2006).…”
Section: Introductionmentioning
confidence: 99%